PROTEOMIC TECHNOLOGY IN THE STUDY OF ENDOMETRIOSIS - V. A. Linde; L. R. Tomay; V. O. Gunko; T. N. Pogorelova; N. V. Ermolova; K. V. Slesareva; L. V. Kolesnikova; I. V. Markaryan; N. N. Skachkov (Медицинский вестник Юга России, 2013)
This review presents the data of the foreign and domestic authors concerning the basic theories of endometriosis and its diagnosis. The current state of proteomic researches on search and identification of markers of an endometriosis is discussed.